of composite powder producing on wear rate of the NiAl-CrB2 plasma coatings. - Полярус, Е.Н. (Problems of Tribology, 2016)
The effect of the method of composite powders producing on the structure and performance of the NiAl-CrB2 plasma coating was investigated. On the basis of complex structural studies of developed materials and coatings are carried out by selection of the optimal technology of composite powder coating materials producing. The results of tribological tests have shown that the coating of powders, obtained by sintering and hot pressing, characterized by lower wear values compared with coatings from conglomerated powders. Keywords: NiAl intermetallic compound, chromium diboride, conglomeration, composite materials and coatings, tribological tests, wear resistance.